Contemporary Global Perspectives on Cooperative Learning – Personal Reflections - Sharan, Yael (Autonomy and Responsibility Journal of Educational Sciences, 2023)
Contemporary Global Perspectives on Cooperative Learning – Personal Reflections Gilies, R. M., Millis, B. & Davidson, N. (2023). Contemporary Global Perspectives on Cooperative Learning. Application Across Educational Contexts. Routledge.